Analysis of granule fracture under biaxial compression. Issue 18 (15th December 2017) - Satone, Hiroshi; Iimura, Kenji; Teraoka, Tsubasa; Hanafusa, Taisuke; Hisatani, Shuhei; Nishiwaki, Masashi; Suzuki, Michitaka
Abstract: In this study, the mechanism of granule fracture under biaxial compression was investigated through both experimental and simulation methods. The results of the experiment indicate that the fracture behavior differs depending on the number of compressional axes. The fracture load under the biaxial condition is smaller than that under the uniaxial condition because in the latter, the compressed granule can be deformed planarly, whereas in the former, the compressed granule can be deformed into only one axial direction that is not compressed. To investigate this phenomenon in detail, finite-element method (FEM) analysis was used to analyze the tensile stress inside granules. The results of the FEM simulation indicate that the dominant factor in fracture phenomenon is tensile stress at the center of granules. From these results, it will be possible to theoretically predict, without any complicated experiments, the likelihood of fracture in granules. Highlights: The fracture load under the biaxial condition is smaller than that under the uniaxial condition. The dominant factor in fracture phenomenon is tensile stress at the center of granules. The fracturing of granules can be estimated by combining FEM simulation and single-axis compression test.